2021
DOI: 10.7196/ajhpe.2021.v13i2.1300
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with emotional exhaustion in undergraduate and postgraduate nursing students

Abstract: The backbone of a caring nurse is compassion, when nurses have feelings of empathy for the suffering of others and understand patients' personal feelings or experiences without being judgemental. [1] As a result, nursing is particularly stressful, [2][3][4] as nurses not only cope with their personal stress but also with secondary forms of stress due to the nature of their interaction with patients and their families. Nursing students may be more vulnerable to the harmful effects of secondary stress, as they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Engelbrecht and Wilke (2021) state that with the increase in perceived stress in nursing students, they have difficulty in perceiving the knowledge and skills required to provide care, and this situation affects their clinical practice. It was reported that it hurt the quality of care (26) reported that clinical practice is a stress-causing factor for nursing students, and the factors affecting this include lack of professional and knowledge, patient care and environmental stress (26,27) Pfeiffer and Grabbe (2022) reported that nursing students had difficulty and hesitation in explaining their traumatic experiences during clinical practice in order to develop an educational model for increasing trauma resilience in the education of nursing students (17). Kelle Dikbaş and Okanlı (2022) reported that the level of STS was high in nurses who could not cope effectively with stress (9).…”
Section: Discussionmentioning
confidence: 99%
“…Engelbrecht and Wilke (2021) state that with the increase in perceived stress in nursing students, they have difficulty in perceiving the knowledge and skills required to provide care, and this situation affects their clinical practice. It was reported that it hurt the quality of care (26) reported that clinical practice is a stress-causing factor for nursing students, and the factors affecting this include lack of professional and knowledge, patient care and environmental stress (26,27) Pfeiffer and Grabbe (2022) reported that nursing students had difficulty and hesitation in explaining their traumatic experiences during clinical practice in order to develop an educational model for increasing trauma resilience in the education of nursing students (17). Kelle Dikbaş and Okanlı (2022) reported that the level of STS was high in nurses who could not cope effectively with stress (9).…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la H1 y la H2, los resultados apoyan el proceso de deterioro de salud de la teoría DRL el contexto de posgrado de enseñanza. Así, la percepción de sobrecarga de trabajo académico actuaría como un elemento favorecedor del malestar académico, en línea con trabajos anteriores (Engelbrecht et al, 2021). Además, se pone de relieve la necesidad de rediseñar las actividades y la metodología para impartir contenidos en las titulaciones de posgrado.…”
Section: Conclusionesunclassified